ANALISIS PENERAPAN SISTEM “MATO” PADA MANAJEMEN PENGGAJIAN KARYAWAN DI RESTORAN PADANG SEDERHANA DI KOTA YOGYAKARTA - Farah Atiqah; Dewita Puspawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The "MATO" system is a profit-sharing system that is unique and privileged in managing Padang Simple restaurant. It is still rare for previous studies to in-depth analyze the application of the "MATO" system, especially in the Padang Simple restaurant in Yogyakarta. This study aims to analyze the application of the "MATO" system in the management of employee payroll at the Padang Simple restaurant, Yogyakarta. The data in this study are primary data obtained through interviews with the manager of the Padang Simple restaurant in Yogyakarta. The data obtained were analyzed using descriptive qualitative methods. The results of the analysis show that the "MATO" system is a combination of a profit-sharing system and a point system in employee payroll. The system is implemented by mutual agreement and becomes a motivation in improving employee performance. Furthermore, related to the proportion of salaries, it was found that the proportion of employee salary distribution in the mato system was divided by 50% for owners and 50% for employees. The proportion is divided from the company's net profit.